Ocena ratingów na polskim rynku obligacji pozaskarbowych - Wrzosek, Piotr (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper presents activities of rating agencies, and bond issuers in the Polish non-treasury bond market. It appears that very few corporate bonds were ever rated by rating agencies, but in recent years about 20% of debt in form of municipal bonds issued on the Polish non-treasury bond market were rated by Fitch Polska S.A. agency. Because of lack of data nothing can be said about the relation of yields to maturity and rating on this market. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 531-540